Naftidrofuryl for intermittent claudication: meta-analysis based on individual patient data. (10th March 2009) - De Backer, T; Vander Stichele, R; Lehert, P; Van Bortel, L
Abstract : Objective To assess the efficacy of naftidrofuryl compared with placebo in treating the symptoms of intermittent claudication. Design Meta-analysis based on individual patient data. Data sources Medline, International Pharmaceutical Abstracts, Embase, Science Citation Index, and the Cochrane trial registers. Reference lists of retrieved articles were checked. Authors and companies were approached for additional information and individual patient data. Inclusion criteria Double blind, randomised controlled trials in patients with intermittent claudication receiving oral naftidrofuryl or placebo and with pain-free walking distance as primary outcome. Data collection Individual patient data were collected from electronic data or from case report forms and checked for integrity. Analysis All randomised patients were analysed following the intention to treat principle. Efficacy was assessed by the ratio of geometric mean of the relative improvement in pain-free walking distance after use of naftidrofuryl compared with placebo. In the analysis of responders, therapeutic success was defined as an improvement of walking distance at baseline by at least 50%. Results In total, 1266 patients were randomised (1083 in the main analysis). The ratio of relative improvement in pain-free walking distance after use of naftidrofuryl compared with placebo was 1.37 (95% confidence interval 1.27 to 1.49). The difference in response rate was 22.3% (95% confidence interval 17.1% to 27.6%) and the number needed to treat for relief of symptoms during six months of treatment was 4.48 (95% confidence interval 3.62 to 5.85). Conclusion This meta-analysis of individual patient data provides evidence that naftidrofuryl has a clinically meaningful effect compared with placebo in improving walking distance in patients with intermittent claudication.